Analisis Penerapan SPBE (Sistem Pemerintahan Berbasis Elektronik) Di Pemerintahan Kabupaten Mamuju Melalui SIPAMANDAR - Annisa, Nur; Rismayanti; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
The implementation of the Electronic-Based Government System (SPBE) is a national strategy to improve the effectiveness of governance and the quality of public services. The Mamuju Regency Government has implemented SPBE through the SIPAMANDAR application as a medium for administrative management and data integration between Regional Apparatus Organizations (OPD). This study aims to analyze the effectiveness of SPBE implementation through SIPAMANDAR in terms of policy, institutional, technological infrastructure, human resources, and its impact on public services. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results show that SIPAMANDAR contributes positively to work efficiency, increased administrative transparency, and ease of access to information. However, its implementation has not been optimal due to limitations in integration between OPDs, uneven human resource readiness, unstable network infrastructure, and a lack of socialization to the community. This study concludes that the optimization of SPBE in Mamuju Regency requires strengthening human resource capacity, improving digital infrastructure, and continuous coordination and evaluation across OPDs.